Randomised double-blind trial of acyclovir and idoxuridine in dendritic corneal ulceration. Issue 10 (October 1980) - Collum, L M; Benedict-Smith, A; Hillary, I B
Abstract : The results of a randomised double-blind clinical trial of 3% acyclovir and 0.5% idoxuridine (IDU) ophthalmic ointments in 60 patients with corneal dendritic ulceration are presented. Ulcers in all 30 patients treated with acyclovir healed compared with 22 (76%) of 29 patients treated with IDU (P < 0.01). Patients treated with acyclovir healed more rapidly (average 4.4 days) than those who received IDU (average 9.2 days) (P < 0.01). No serious side effects were observed, though transient stinging was recorded in 8 patients receiving acyclovir and in 2 patients receiving IDU. Other side effects in the IDU treated group were watering in 2 patients and superficial punctate erosions in 6 patients.